Retrofit em baldios industriais urbanos e o complexo Matarazzo, Jaguariaíva – PR - Correia, Beatriz Silva (2015)
This thesis addresses practices of retrofit, a term originating in product engineering, convened by the Architecture and Urbanism in the urgent need to rehabilitate, renovate, restore, restructure, remodel, regenerate, protecting historical aspects of a building, incorporating appropriate technology to present days. The objective was to explore relevant aspects of these projective techniques in urban industrial brownfields, according to the socioeconomic diversity and sustainable local development. For this, concepts, models and situations of consumption and appropriation of these resources were prized to industrial architectural typologies. They are taken up by the ideas of Eduardo E. Lozano and Amartya Sen, highlighting the sensorial and socioeconomic diversity as drivers of development with quality of life. The research is qualitative and elaborates a proposal for a retrofit to an underused industrial brownfield, inserted in the municipality of Jaguariaíva - PR. For that, unique relationships in interventions to similar architectural objects were connected, either by displaying space or heterogeneity in individual appropriation of these realities. Thereafter, for the case of the ancient Slaughterhouse Matarazzo, feasible interferences by retrofit were recommended. They would permit reclaim the historical past in a contemporary language. In this sense, the proposed technical resources were pursued to readjust the facilities, so that they might encourage the integration of the socio-economic sustainability and development as freedom. It is recommended for the built set, the redistribution of spaces for other activities, assigning them new vocations that can move between transience and permanence. It is concluded that the proposed retrofit for Matarazzo Complex formulated based on theoretical studies and on the selected and analyzed examples, allows rescue the history, favoring the sectors of trade and services, reviving urban life by granting it quality.